Functional Recovery following Repair of Long Nerve Gaps in Senior Patient 2.6 Years Posttrauma - Christian A. Foy, MD; William F. Micheo, MD; Damien P. Kuffler, PhD (Plastic and Reconstructive Surgery, Global Open, 2021)
Summary:. Sensory nerve grafts are the clinical “gold standard” for repairing peripheral nerve gaps. However, reliable good-to-excellent recovery develops only for gaps less than 3–5 cm, repairs performed less than 3–5 months posttrauma, and patients aged less than 20–25 years. As the value of any variable increases, the extent of recovery decreases precipitously, and if the values of any two or all increase, there is little to no recovery. One 9-cm-long and two 11-cm-long nerve gaps in a 56-year-old patient were repaired 2.6 years posttrauma. They were bridged with two sensory nerve grafts within an autologous platelet-rich plasma-filled collagen tube. Both were connected to the proximal ulnar nerve stump, with one graft end to the distal motor and the other to the sensory nerve branches. Although presurgery the patient suffered chronic level 10 excruciating neuropathic pain, it was reduced to 6 within 2 months, and did not increase for more than 2 years. Motor axons regenerated across the 9-cm gap and innervated the appropriate two measured muscles, with limited muscle fiber recruitment. Sensory axons regenerated across both 11-cm gaps and restored normal topographically correct sensitivity to stimuli of all sensory modalities, including static two-point discrimination of 5 mm, and pressure of 2.83 g to all regions innervated by both sensory nerves. This novel technique induced a significant long-term reduction in chronic excruciating neuropathic pain while promoting muscle reinnervation and complete sensory recovery, despite the values of all three variables that reduce or prevent axon regeneration and recovery being simultaneously large.